(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Physical training is considered an integral part of combat training and serves to form military personnel’s physical qualities and to be ready for combat tasks. This article provides information on the physical training of military personnel, its organization, conduct, material support, and keeping records of physical training.